Performance and In‐Situ FTIR Evaluation of Pt−Sn/C Electrocatalysts with Several Pt : Sn Atomic Ratios for the Ethanol Oxidation Reaction in Acidic Media. Issue 22 (13th September 2018) - González‐Quijano, D.; Pech‐Rodríguez, W. J.; González‐Quijano, J. A.; Escalante‐García, J. I.; Morais, C.; Napporn, T. W.; Rodríguez‐Varela, F. J.
Abstract: Pt−Sn/C electrocatalysts with nominal Pt : Sn atomic ratios of 1 : 1, 2 : 1 and 3 : 1 were synthesized via the polyol method. The effects of the atomic ratios on their catalytic activity for the ethanol oxidation reaction (EOR) in acidic media was evaluated and compared to a Pt/C electrocatalyst obtained by the same procedure. The differences in reaction mechanism between the alloys and Pt/C were elucidated by in‐situ FTIR measurements. XRD characterization of the Pt−Sn/C electrocatalysts showed a degree of alloying ranging between 27 and 54 % (from Vegard's law), while crystallite sizes close to 2.2 nm were determined with the Scherrer equation. Pt : Sn atomic ratios of 1 : 1, 1.6 : 1 and 2.4 : 1 were found experimentally via EDS analysis, fairly close to the nominally expected values. Electrochemical evaluation indicated that the alloy having a 1 : 1 ratio has the highest electrocatalytic activity for EOR. In‐situ FTIR characterization showed that the Pt−Sn/C alloys promote the oxidation of ethanol via a triple parallel pathway: one path involving the directly conversion of COL (linearly‐bonded CO) to CO2, while the second proceeds via the reaction of AAL (acetaldehyde) into COL and later to CO2, and the third involves the formation of AA (acetic acid) from adsorbed acetate that may be produced from AAL. Such mechanism promoted the EOR at more negative potentials at the alloys, also delivering higher current densities, relative to Pt/C. Thus, the inclusion of Sn in the Pt structure enhanced the catalytic activity for the EOR in acidic media. Abstract : Teaching an old dog new tricks : Pt−Sn/C electrocatalysts with controlled Pt : Sn atomic ratios are synthesized. The effects of the atomic ratios on their activity for the ethanol oxidation reaction in acidic media is evaluated and compared to Pt/C. In‐situ FTIR characterization showed that the Pt−Sn/C alloys promote the oxidation of ethanol via a triple parallel pathway. The highest catalytic activity is found for the alloy with a 1 : 1 Pt : Sn ratio.